2006
DOI: 10.1089/tmj.2006.12.324
|View full text |Cite
|
Sign up to set email alerts
|

Telehomecare for Vulnerable Populations: The Evaluation of New Models of Care

Abstract: The use of telehomecare has the potential to facilitate access to healthcare services for vulnerable populations. However, evidence on the implications of telehomecare on various aspects related to patients, healthcare professionals, organizations, and healthcare systems is still limited. Assessing the various effects of telehomecare for these different groups of stakeholders is thus an essential step to ensure future integration of this technology into mainstream healthcare services. A synthesis of lessons le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 16 publications
0
38
0
1
Order By: Relevance
“…20 One publication reported findings from two studies conducted in Canada and France. 15 In general, staff held positive views about using RMT but expressed concerns about workload and staffing. 13,15,24 In some studies, nurses reported greater professional autonomy with RMT use.…”
Section: Key Question 2 Views Of Primary Care Administrator and Stafmentioning
confidence: 99%
See 3 more Smart Citations
“…20 One publication reported findings from two studies conducted in Canada and France. 15 In general, staff held positive views about using RMT but expressed concerns about workload and staffing. 13,15,24 In some studies, nurses reported greater professional autonomy with RMT use.…”
Section: Key Question 2 Views Of Primary Care Administrator and Stafmentioning
confidence: 99%
“…15 In general, staff held positive views about using RMT but expressed concerns about workload and staffing. 13,15,24 In some studies, nurses reported greater professional autonomy with RMT use. 15,20,23,24 The need for better integration between RMT data and the patients' EHRs was also noted.…”
Section: Key Question 2 Views Of Primary Care Administrator and Stafmentioning
confidence: 99%
See 2 more Smart Citations
“…국외의 경우 공공부문의 서비스로 저소득층을 위해서는 홈 모니터링을 추진하고 있으며, 기술개발 [10], 모델 개발 [11], 수 용성 및 지속성 [12]등의 연구가 이루어졌다. 국내에서는 스마 트 홈과 관련하여 기술적 요인 [13], 공간적 요소 [14], 서비스 제 공 경험분석 [15], 정책적 함의 [16] Table 2와 같다.…”
unclassified